ОСОБЕННОСТИ РЕАЛИЗАЦИИ КОНЦЕПТА «РАДОСТЬ» В ЛЕКСИКЕ АНГЛИЙСКОГО ЯЗЫКА: КОГНИТИВНО-ЛИНГВОКУЛЬТУРНЫЙ АНАЛИЗ - Таженова, С.Б. (SCIENCE and SOCIETY, 2025)
The article analyzes the implementation of the concept JOY in English vocabulary. It considers the structure of the semantic field, core and peripheral nominations, word-formation models (joyful, joyless, killjoy), collocations (tears of joy, leap for joy), and idioms (on cloud nine, over the moon). It is shown that religious discourse tends to use elevated forms (joyous, rejoice), while colloquial speech abounds in expressive clichés. The novelty of the study lies in a comprehensive description of the JOY field at lexical-semantic and phraseological levels.